Local vertical movements of the ground surface based on the results of 18-year extensometric observations in Poltava - Pavlyk, Volodymyr; Kutnyi, Andriy; Zalyvadnyi, Mykola; Babych, Tetiana (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2026)
The results of 18-year observations of the vertical component of local ground surface dynamics using a quartz extensometer of the Poltava Gravimetric Observatory are presented. The instrument is installed at a geodynamic polygon in Poltava and allows monitoring of vertical displacements of the soil layer at a depth of 0.5 m from the surface with an accuracy of 10-6 m in order to study the influence of external factors of hydrometeorological origin on the dynamics of the most mobile upper soil layer. It was established that the dominant component of vertical movements is the seasonal component with an average annual amplitude of 1.726±0.045 mm, the moment of maximum elevation of the ground, which falls on 114.32 ±0.06 days from the beginning of the year (April 24) and a period of 364.42±0.30 days. Depending on the climatic features of a particular year of observations, the magnitude of periodic local vertical displacements varies from 1.0 mm to 5.5 mm, and the moments of maximum elevation of the ground occur in the period from March 28 to May 16. Seasonal vertical movements are primarily caused by periodic variations in the moisture of medium loamy soils of the polygon. If the soil moisture exceeds its maximum molecular moisture capacity, this factor ceases to act on vertical movements. Fluctuations in groundwater levels are not the cause of vertical movements, although they occur in phase with them. It is shown that the abnormally dry summer of 2024 in Poltava caused the lowest vertical position of the ground surface for the entire observation period. Ignoring vertical movements of hydrometeorological origin can lead to incorrect interpretation of the results of the study of tectonic and technogenic deformations of the ground surface.